Determining the Essential Characteristics for Effective College Teaching - Christopher Eck; Jeremy Robinson; Ki Cole (Journal of the Scholarship of Teaching and Learning, 2024)
Higher education institutions continually increase the demands on college instructors. Yet, all too often, many college instructors have had little to no preparation for teaching in higher education. What is needed is a comprehensive and clear list of characteristics expected of effective college teachers, both in-person and online, comprised by those who are focused on studying the subject matter deeply. To assess the characteristics deemed essential for college instructors to possess, a nationwide, modified Delphi technique was employed, eliciting opinions from an established panel of experts. At the conclusion of a three-round Delphi study, 46 of the 55 original items submitted by the panelists reached consensus of agreement. The 46 items were then categorized to establish six overarching themes associated with effective college teaching. The categorized themes and characteristics determined in the study of effective college teachers should be used as a comprehensive and clear list to provide college faculty with expectations of effective teaching. Additional research is needed to convert the items found in this study into an effective college teaching instrument. Such an instrument should be validated for use across academia as a starting point for the development, training, and support of future and current college teachers.